Bovine embryo-oviduct interaction in vitro reveals an early cross talk mediated by BMP signaling - Garcia, Elina Vanesa (2017)
Signaling components of bone morphogenetic proteins (BMPs) are expressed in an anatomically and temporally regulated fashion in bovine oviduct. However, a local response of this signaling to the presence of the embryo has yet to be elucidated. The aim of the present study was to evaluate if early embryo-oviduct interaction induces changes in the gene expression of BMP signaling components. For this purpose, we used an in vitro co-culture system to investigate the local interaction between bovine oviductal epithelial cells (BOEC) from the isthmus region with early embryos during two developmental periods: before (from the 2-cell to 8-cell stage) or during (from the 8-cell to 16-cell stage) the main phase of embryonic genome activation (EGA). Exposure to embryos, irrespective of the period, significantly reduced the relative abundance of BMPR1B, BMPR2, SMAD1, SMAD6 and ID2 mRNAs in BOEC. In contrast, embryos that interacted with BOEC before EGA showed a significant increase in the relative abundance of SMAD1 mRNA at the 8-cell stage compared to embryos cultured without BOEC. Moreover, embryos at the 16-cell stage that interacted with BOEC during EGA showed a significant increase in BMPR1B, BMPR2 and ID2 mRNA. These results demonstrate that embryo-oviduct interaction in vitro induces specific changes in the transcriptional levels of BMP signaling, causing a bidirectional response that reduces the expression levels of this signaling in the oviductal cells while increases them in the early embryo. This suggests that BMP signaling pathway could be involved in an early cross talk between the bovine embryo and the oviduct during the first stages of development.